Association of Idiopathic Subglottic Stenosis and Body Mass Index. (23rd August 2013) - Lalich, Ian J.; Kasperbauer, Jan L.; Maldonado, Fabien; Ekbom, Dale C.; Edell, Eric S.
Abstract : Objectives: 1) Describe factors associated with development, disease control, and rate of recurrence in patients with Idiopathic Subglottic Stenosis (ISS). 2) Evaluate the relationship between Body Mass Index (BMI) and ISS. Methods: A retrospective chart review was performed for patients treated at the Mayo Clinic Rochester between 1996 and December 2012. All patients 16 years and older with a clinical diagnosis and/or treatment of ISS were reviewed. Patients with an identifiable etiology for stenosis including trauma, prior neck surgery, previous tracheostomy, multiple intubations (>6 lifetime intubations), prolonged intubation (>1 week), Wegener's Granulomatosis, or an antecedent explanation for their stenosis were excluded. Outcome measurements included symptom free interval, recurrence, and number of procedures performed. Results: Features were collected on 182 female and 4 male patients. At diagnosis, 121 (65%) patients were overweight, and 76 (41%) patients were obese. The mean BMI at first surgery was 28.7 kg/m2. Ninety‐one patients experienced at least one recurrence at a mean of 2.3 years following treatment. Mean number of recurrences, relative to follow‐up interval, for class BMI >30.0 kg/m2 was 1.6 recurrences/year compared with 1.0 recurrences/year for BMI < 30 kg/m2 ( P = 0.050). Increasing incidence of the following comorbidities was significantly associated with increases in BMI: heartburn ( P = 0.012), gastroesophageal reflux disease ( P = 0.011), hypertension ( P = <0.001), cardiac history ( P = 0.045), hyperlipidemia/dyslipidemia ( P = <0.001), and diabetes mellitus ( P = 0.004). Conclusions: ISS patients with elevated BMI appear to have an increased risk of recurrent disease. Encouraging lifestyle change and weight reduction may assist in disease control.